“Establecimiento de métodos y técnicas de ahorro energético aplicado al proceso de secado de madera”. - Solis Toscano, Jonathan Ronny (2020)
The purpose of this research was to establish energy saving methods and techniques applied to the wood drying process. For this, a data recording was carried out with a charge analyzer during 3 days in the cutting and drying area at the company BALSARIVER CIA. LTDA., which is located on km 2.5 Quevedo - Valencia highway. As an alternative of solution, the installation of soft starters in the drying area was carried out, since the area consumes a higher level of energy. The results show that the average energy consumption in the wood cutting process is 75.98 kWh/day, while the drying process is 116.64 kWh/day, so representing a total cost of $ 843.38 and $ 1294.66 of energy consumption per month, considering 30 days of work. The drying process is the stage of the production process of the company that represents the highest energy consumption, because it requires a greater amount of work hours to achieve that wood reaches the optimum humidity level for its processing. The installation of soft starters represents a substantial saving of electric energy consumption in the wood drying process due to starters adjust the voltage and the necessary current in order to get stability and avoid variation of energy caused by repetitive starts. That is why it is recommended to promote the use of soft starters in both processes of the company just because they produce energy savings and economic savings at the same time.